The Role of Transformational Leadership and Psychological Capital in the Hotel Industry: A Sustainable Approach to Reducing Turnover Intention - Daria Gom; Tek, Yew Lew; Mary Monica Jiony; Geoffrey Harvey Tanakinjal; Stephen Laison Sondoh Jr. (MDPI, 2021)
With the high level of importance placed on service delivery and the elevated turnover rate experienced in the hotel industry, this study was conducted to explore the influences of perceived transformational leadership on the cross-cultural psychological capital and turnover intentions of frontline employees working in four- and five-star hotels in Sabah, Malaysia. Data were collected from 162 frontline employees using the purposive sampling method. Partial least squares structural equation modeling (PLS-SEM) was performed to test the hypothesized relationships. The findings clearly demonstrate that transformational leadership positively affects cross-cultural psychological capital and negatively influences turnover intention. Cross-cultural psychological capital, on the other hand, has no substantial link with turnover intention and does not act as a mediator between transformative leadership and turnover intention. This study extends the hospitality literature by offering a new conceptual model representing the perceptions of frontline employees toward transformational leadership and cross-cultural psychological capital that influence the turnover intention of these employees based on the job demands–resources and conservation of resources theories. These findings have implications for the advancement of transformational leadership and cross-cultural psychological capital toward a sustainable approach to reducing employee turnover in the hotel industry.